Companionship for women/birthing people using antenatal and intrapartum care in England during COVID-19: a mixed-methods analysis of national and organisational responses and perspectives. Issue 1 (11th January 2022) - Thomson, Gill; Balaam, Marie-Claire; Nowland (Harris), Rebecca; Crossland, Nicola; Moncrieff, Gill; Heys, Stephanie; Sarian, Arni; Cull, Joanne; Topalidou, Anastasia; Downe, Soo
Abstract : Objectives: To explore stakeholders' and national organisational perspectives on companionship for women/birthing people using antenatal and intrapartum care in England during COVID-19, as part of the Achieving Safe and Personalised maternity care In Response to Epidemics (ASPIRE) COVID-19 UK study. Setting: Maternity care provision in England. Participants: Interviews were held with 26 national governmental, professional and service-user organisation leads (July–December 2020). Other data included public-facing outputs logged from 25 maternity Trusts (September/October 2020) and data extracted from 78 documents from eight key governmental, professional and service-user organisations that informed national maternity care guidance and policy (February–December 2020). Results: Six themes emerged: 'Postcode lottery of care' highlights variations in companionship and visiting practices between trusts/locations, 'Confusion and stress around 'rules'' relates to a lack of and variable information concerning companionship/visiting, 'Unintended consequences' concerns the negative impacts of restricted companionship or visiting on women/birthing people and staff, 'Need for flexibility' highlights concerns about applying companionship and visiting policies irrespective of need, ''Acceptable' time for support' highlights variations in when and if companionship was 'allowed' antenatally and intrapartum and 'Loss of human rights for gain in infection control' emphasises how a predominant focus on infection control was at a cost to psychological safety and human rights. Conclusions: Policies concerning companionship and visiting have been inconsistently applied within English maternity services during the COVID-19 pandemic. In some cases, policies were not justified by the level of risk, and were applied indiscriminately regardless of need. There is an urgent need to determine how to sensitively and flexibly balance risks and benefits and optimise outcomes during the current and future crisis situations.